Post-Pandemic Behavior: Continuance Intention of Baby Boomer and X Generation as New Users of Online Shopping Platforms during COVID-19 - Allicia Deana Santosa; Nuryanti Taufik (University of Merdeka Malang, 2023)
The Covid-19 pandemic has led to an unavoidable surge in the use of digital technology due to social restrictions and lockdowns. Various restrictions on activities during the COVID-19 quarantine period had resulted in many new users of digital services for daily activities and needs, including the elderly generation such as the X Generation and baby boomers, who before the pandemic were often considered as a generation that was difficult to accept technological change. In the midst of the COVID-19 pandemic, the baby boomers and X Generation have begun to adopt and use various digital applications, one of which is e-commerce, to make online purchases. With the return to the post-pandemic situation and routine, we wanted to test the continuance intention of X Generation and baby boomers in using e-commerce for online shopping. This study needs to be done since the data shows that the average number of online purchases issued by X Generation and baby boomers is greater than other generations. Unfortunately, the literature and previous research on the post-pandemic behavior of baby boomers and X generation for online shopping activities are still very limited, so this research is expected to contribute to a wider literature. The survey was conducted on 198 people aged 40-76 years who had made online purchases in e-commerce during the COVID-19 pandemic using Structural Equation Modeling.